GE_GERICHTE C/15095/2015 vom 30. Oktober 2015 - GE Cour de justice (2015)
AVANCE DE FRAIS; TARIF(EN GÉNÉRAL); FORCE OBLIGATOIRE(LOI/TRAITÉ/PLAN); ORGANE(PERSONNE MORALE); DISSOLUTION DE LA SOCIÉTÉ; VALEUR LITIGIEUSE | CPC.95; RTFMC.26; CO.731b